Evaluation of contralateral arterial flow compensation using transcranial Doppler in acute internal carotid artery occlusion and implications for neurological outcome - Yichen Wang; Hong Chang; Peng Bai; Jin Chen (Scientific Reports, 2025)
Abstract Acute internal carotid artery occlusion (AICAO) can result in malignant cerebral edema and unfavorable patient outcomes. This study evaluated the utility of transcranial Doppler (TCD) in assessing contralateral flow compensation and predicting outcomes in patients with AICAO. We enrolled 51 patients within 6 h of symptom onset and conducted TCD examinations to evaluate collateral circulation. Among the 51 patients, 40 (78.4%) had collateral flow. TCD showed excellent agreement with magnetic resonance angiography (MRA)/CT angiography (CTA) in assessing anterior communicating artery (ACoA) status (kappa = 0.873, p < 0.001). Our findings indicated that the absence of collaterals (OR = 7.649, p = 0.032), younger age (OR = 0.907, p = 0.048), and lower Alberta Stroke Program Early CT Score 24 h after onset (ASPECTs1) (OR = 0.276, p = 0.025) were independent predictors of malignant cerebral edema. Additionally, advanced age, elevated National Institutes of Health Stroke Scale Score (NIHSSs) in the Emergency Department, sole extracranial-to-intracranial collateral circulation (EICC), and absence ACoA were independently associated with worse outcomes (all p < 0.05). In conclusion, TCD evaluation of collateral circulation in AICAO patients can effectively predict the risk of malignant cerebral edema, with ACoA presence correlating with favorable outcomes and sole EICC linked to poorer prognosis. While age, NIHSSs and ASPECTs also contribute, TCD’s assessment of collaterals provides key insights for patient management.